A Cross-sectional Study of Antecedents and Consequence of Panic Buying Behavior: The Moderating Effect of COVID-19 Rumors. (September 2022) - Waseem, Muhammad Adnan; Waqas, Muhammad; Irfan, Irfan; Abdullah, Ibrahim; Wajid, Nauman
The novel corona virus pandemic has influenced people buying behaviors. Due to the significant psychological and behavioral impact of COVID-19 on society, this study aimed to examine the determinants of panic buying behavior and a resultant psychological outcome in the form of a sense of security. The purpose of this study is to investigate the effect of COVID-19 caller ringback tone (CRT) experiences, that is, informational and stimulation experience, on the panic buying behavior and how rumors moderate this relationship. This research is quantitative and uses a purposive sampling method to collect the survey-based data from 264 respondents. The researchers analyzed the data using Partial Least Square Structural Equation Modeling (PLS-SEM). The results of data analysis indicated that the informational and stimulation experience of COVID-19 CRT had a significant influence on panic buying behavior which further resulted in a sense of security in public. This study could not find evidence of the moderating role of rumors in the relationship between COVID-19 CRT experiences and panic buying behavior. The findings highlight the role of the COVID-19 CRT in causing panic buying behavior and resultant psychological outcome and thus provide implications for policymakers on the control of panic buying under COVID-19.